Homoousia - sprog, krop, trinitet i mediefilosofisk perspektiv - Pallesen, Carsten (Dansk teologisk tidsskrift, 2016)
Resumé From the vantage point of body and language in contemporary philosophy of media the article suggests a reinterpretation of the key term homoousia of the Nicene Creed. The concept of homoousia serves as a guideline for Martin Luther’s understanding of the trinity in dialogical rather than narrative terms. The article explores the hermeneutical dimension of body metaphors and language in the Trinitarian faith in a trajectory of reception from Luther to Post-Hegelian theories from Hans-Georg Gadamer to Niklas Luhman, Jean-Luc Nancy and Giorgio Agamben and in contemporary theological interpretations by Carl Andresen, Günter Bader, Eberhard Jüngel and Phillipp Stoellger.